Między „ziemią obiecaną” a „złym miastem” – cała (?) prawda o Łodzi w publicystyce i prasie warszawskiej, cz. 2 - Kołodziej, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article focuses on the metaphorical term used in order to describe Łódź at the turn of nineteenth century. Apart from conventional names, such as “Polish Manchester” or “the other Babel”, journalists from Warsaw searched for fresh metaphors, which were supposed to establish a unique character of the cottonopolis. The journalist who coined the term “linear city” referred to the territorial expansion of the metropolis (underlining the pace of development), as well as the topography of the city. A lot of attention was also paid to the contrasts in Łódź (“an interesting city”), where wealth and poverty existed in an odd symbiosis, even within the space of one street. The journalists from the capital, though perceived Łódź through its industrial character, paid insufficient attention to the biggest group of citizens – workers. Only one article, written by Mieszkowski, stands out as a vast monograph. The description of workers’ lives completes the bigger picture of “the home of hectic work”. The writers frequently underlined the provincialism of the city. It was its industrial character which made this probably most cosmopolitan of Polish cities to be perceived as provincial, due to its poor cultural life and superiority of industry over art. Similarly to Reymont, who ironically entitled his novel “Promised Land”, one journalist called the city “a major cultural centre”.